Natural mortality from poor condition in Atlantic cod ( Gadus morhua) - Dutil, Jean-Denis; Lambert, Yvan (Canadian Journal of Fisheries and Aquatic Sciences, 2000)
The extent of energy depletion was assessed in Atlantic cod (Gadus morhua) in spring and early summer (1993-1995) to assess relationships between poor condition and natural mortality. Several indices of condition were compared in wild fish in the northern Gulf of St. Lawrence and in fish exposed to a prolonged period of starvation in laboratory experiments. Discriminant analyses classified only a small fraction of the wild fish as similar to cod that did not survive and a much larger fraction as similar to cod that survived starvation. This percentage increased from April to May and peaked in June 1993 and 1994. Condition factor and muscle somatic index allowed a clear distinction between live and dead fish. Muscle lactate dehydrogenase activity suggested that cod had experienced a period of negative growth early in 1993, 1994, and 1995. Fish classified as similar to starved individuals were characterized by a higher gonad to liver mass ratio than others. Reproduction may have a negative impact on survival not only in spring but also later into summer, as some individuals were found not to have recovered by late summer. This study shows that natural mortality from poor condition contributed to lower production in the early 1990s.